A working party report on the life cycle costing of corrosion in the oil and gas industry a guideline - Jackman, P. S. (Maney for the European Federation of Corrosion on behalf of the Institute of Materials, Minerals and Mining, 2003)
This EFC publication addresses the important subject of the analysis of life cycle cost of corrosion as it may be applied in the oil and gas production industries. The publication is not intended to be a stand-alone document but to guide the analyst to corrosion-specific subjects for inclusion in an overall analysis. The process of life cycle costing has recently been standardised in ISO 15663, Parts 1 to 3.
Keywords: Metals -- Corrosion fatigue.; Pipelines -- Corrosion.; elektronické knihy; electronic books